Gender Inequality in the Novel the Dressmaker by Rosalie Ham (Sastra Inggris UNPAM, 2025)
The study aims at describing gender inequality in the Novel The Dressmaker By Rosalie Ham”. The object is a novel entitled The Dressmaker by Rosalie Ham. The purpose of this study is to analyze the gender inequality that exists in the novel and how gender inequality affects the main characters and the people around her. This study uses a qualitative method in which all the data that has been collected is presented in the form of descriptive analysis. This study is guided by the theory of Lorber (2010) in her book Gender Inequality: Feminist Theories and Politics. There are two results of this research namely, the first is about gender inequality experienced by the main characters in the novel and the second is about how the main characters deal with it. The gender inequality reflected in the novel The Dressmaker are in the form of sexual violence, misogyny, and men dominance. This research also found some ways that were done by the protagonist to deal with gender inequality such as avoidance, self-defense, self-hatred, and self-proving